CAR Triggered Release of Type-1 Interferon Limits CAR T-Cell Activities by an Artificial Negative Autocrine Loop - Dennis Christoph Harrer; Charlotte Schenkel; Valerie Bezler; Marcell Kaljanac; Jordan Hartley; Markus Barden; Hong Pan; Astrid Holzinger; Wolfgang Herr; Hinrich Abken (Cells, 2022)
The advent of chimeric antigen receptor (CAR) T cells expedited the field of cancer immunotherapy enabling durable remissions in patients with refractory hematological malignancies. T cells redirected for universal cytokine-mediated killing (TRUCKs), commonly referred to as “fourth generation” CAR T-cells, are designed to release engineered payloads upon CAR-induced T-cell activation. Building on the TRUCK technology, we aimed to generate CAR T-cells with a CAR-inducible artificial, self-limiting autocrine loop. To this end, we engineered CAR T-cells with CAR triggered secretion of type-1 interferons (IFNs). At baseline, IFNα and IFNβ CAR T-cells showed similar capacities in cytotoxicity and cytokine secretion compared to conventional CAR T-cells. However, under “stress” conditions of repetitive rounds of antigen stimulation using BxPC-3 pancreas carcinoma cells as targets, anti-tumor activity faded in later rounds while being fully active in destructing carcinoma cells during first rounds of stimulation. Mechanistically, the decline in activity was primarily based on type-1 IFN augmented CAR T-cell apoptosis, which was far less the case for CAR T-cells without IFN release. Such autocrine self-limiting loops can be used for applications where transient CAR T-cell activity and persistence upon target recognition is desired to avoid lasting toxicities.